Gene cloning and DNA analysis : an introduction - Brown, T. A. (Terence A.) (Oxford ; Hoboken, NJ : Wiley-Blackwell, 2010)
(Publisher-supplied data) Known world-wide as the standard introductory text to this important and exciting area, the sixth edition of Gene Cloning and DNA Analysis addresses new and growing areas of research whilst retaining the philosophy of the previous editions. Assuming the reader has little prior knowledge of the subject, its importance, the principles of the techniques used and their applications are all carefully laid out, with over 250 clearly presented four-colour illustrations. In addition to a number of informative changes to the text throughout the book, the final four chapters have been significantly updated and extended to reflect the striking advances made in recent years in the applications of gene cloning and DNA analysis in biotechnology. Gene Cloning and DNA Analysis remains an essential introductory text to a wide range of biological sciences students; including genetics and genomics, molecular biology, biochemistry, immunology and applied biology. It is also a perfect introductory text for any professional needing to learn the basics of the subject. All libraries in universities where medical, life and biological sciences are studied and taught should have copies available on their shelves. " ... the book content is elegantly illustrated and well organized in clear-cut chapters and subsections ... there is a Further Reading section after each chapter that contains several key references ... What is extremely useful, almost every reference is furnished with the short but distinct author's remark." --Journal of Heredity, 2007 (on the previous edition)
Part I The basic principles of gene cloning and DNA analysis -- Why gene cloning and DNA analysis are important -- Vectors for gene cloning : plasmids and bacteriophages -- Purification of DNA from living cells -- Manipulation of purified DNA -- Introduction of DNA into living cells -- Cloning vectors for E. coli -- Cloning vectors for Eukaryotes -- How to obtain a clone of a specific gene -- The polymerase chain reaction -- Part II The applications of gene cloning and DNA analysis in research -- Sequencing genes and genomes -- Studying gene expression and function -- Studying genomes -- Part III The applications of gene cloning and DNA analysis in biotechnology -- Production of protein from cloned genes -- Gene cloning and DNA analysis in medicine -- Gene cloning and DNA analysis in agriculture -- Gene cloning and DNA analysis in forensic science and archaeology.
Includes bibliographical references and index.
MNS
Keywords: Molecular cloning; Nucleotide sequence; DNA -- Analysis; Cloning, Molecular; DNA, Recombinant -- analysis; Sequence Analysis, DNA; Pharmacy